Modern Comprehensive Metabolomic Profiling of Pollen Using Various Analytical Techniques - Krejčí, Petra; Žingor, Zbyněk; Balarynová, Jana; Čevelová, Andrea; Tesárek, Matěj; Smýkal, Petr; Bednář, Petr (Molecules (Basel, Switzerland), 2025)
Pollen is a cornerstone of life for plants. Its durability, adaptability, and complex design are the key factors to successful plant reproduction, genetic diversity, and the maintenance of ecosystems. A detailed study of its chemical composition is important to understand the mechanism of pollen-pollinator interactions, pollination processes, and allergic reactions. In this study, a multimodal approach involving Fourier transform infrared spectrometry (FTIR), direct mass spectrometry with an atmospheric solids analysis probe (ASAP), matrix-assisted laser desorption/ionization (MALDI) and ultra-high-performance liquid chromatography-mass spectrometry (UHPLC-MS) was applied for metabolite profiling. ATR-FTIR provided an initial overview of the present metabolite classes. Phenylpropanoid, lipidic, and carbohydrate structures were revealed. The hydrophobic outer layer of pollen was characterized in detail by ASAP-MS profiling, and esters, phytosterols, and terpenoids were observed. Diacyl- and triacylglycerols and carbohydrate structures were identified in MALDI-MS spectra. The MALDI-MS imaging of lipids proved to be helpful during the microscopic characterization of pollen species in their mixture. Polyphenol profiling and the quantification of important secondary metabolites were performed by UHPLC-MS in context with pollen coloration and their antioxidant and antimicrobial properties. The obtained results revealed significant chemical differences among Magnoliophyta and Pinophyta pollen. Additionally, some variations within Magnoliophyta species were observed. The obtained metabolomics data were utilized for pollen differentiation at the taxonomic scale and provided valuable information in relation to pollen interactions during reproduction and its related applications.
Keywords: pollen; atmospheric solids analysis probe; Pollen; ultra-high-performance liquid chromatography; spektroskopie infračervená s Fourierovou transformací; metabolomika; Metabolomics; matrix-assisted laser desorption/ionization; secondary metabolite; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; metabolom; pyl; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; Metabolome; Spectroscopy, Fourier Transform Infrared; infrared spectrometry; Pinophyta; metabolomics; spektrometrie hmotnostní - ionizace laserem za účasti matrice; mass spectrometry; taxonomic differentiation; metabolite profiling; Magnoliophyta